Development and Testing of an Algorithm to Prevent Medical Device-Related Pressure Injuries - Yeong-Mi Seong RN, MS; Hyejin Lee RN, PhD; Ji Min Seo RN, PhD (SAGE Publishing, 2021)
We developed and tested the effectiveness of an algorithm to prevent medical device-related pressure injuries in intensive care unit patients. It was developed in four stages: literature review and analysis of medical records; preliminary algorithm development; validation of the preliminary algorithm by experts in two rounds; and practical feasibility verification of the revised algorithm by 109 intensive care unit nurses. To verify the algorithm's effectiveness, we compared the incidence of medical device-related pressure injuries between 324 patients without algorithm application (control group) and 312 patients with algorithm application (experimental group). The outcomes were skin inspection of the medical device attachment, pressure injury evaluation, and implementation of pressure injury-preventive nursing care, based on the medical device type. The incidence rates were 1.46 per 100 devices (control group) and 1.19 per 100 devices (experimental group). Since there was no homogeneity in the previous score of the Braden scale in the experimental and control groups, the results regarding the incidence of pressure damage after applying the algorithm should be interpreted with care. Applying this algorithm was a safe intervention that helped prevent medical device-related pressure injuries in this population.